2016
DOI: 10.1016/j.prro.2015.10.023
|View full text |Cite
|
Sign up to set email alerts
|

The role of elective nodal irradiation for esthesioneuroblastoma patients with clinically negative neck

Abstract: Purpose Although adjuvant radiation to the tumor bed has been reported to improve the clinic outcomes of esthesioneuroblastoma (ENB) patients, the role of elective neck irradiation (ENI) in clinically node negative (N0) patients remains controversial. Here, we evaluated the effects of ENI on neck nodal relapse risk in ENB patients treated with radiotherapy as a component of multi-modality treatment. Methods and Materials Seventy-one N0 ENB patients irradiated at XXXXXXXXX between 1970 and 2013 were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
43
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 23 publications
7
43
2
Order By: Relevance
“…Although these data emphasize the necessity of bilateral treatment when considering elective neck therapy, much controversy exists surrounding the efficacy of elective neck irradiation or dissection in managing patients with ONB . The most compelling evidence against elective neck therapy stems from the apparent lack of improved survival outcomes in patients who undergo elective neck irradiation, despite achieving excellent regional control . The present study demonstrates 100% regional control after elective neck irradiation, which agrees with previous studies; but these data are too underpowered to draw survival or disease‐control conclusions.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Although these data emphasize the necessity of bilateral treatment when considering elective neck therapy, much controversy exists surrounding the efficacy of elective neck irradiation or dissection in managing patients with ONB . The most compelling evidence against elective neck therapy stems from the apparent lack of improved survival outcomes in patients who undergo elective neck irradiation, despite achieving excellent regional control . The present study demonstrates 100% regional control after elective neck irradiation, which agrees with previous studies; but these data are too underpowered to draw survival or disease‐control conclusions.…”
Section: Discussionsupporting
confidence: 84%
“…Researchers have speculated that the midline nature of ONBs and observed bilateral nodal involvement likely warrant bilateral nodal therapy of the neck, particularly when considering elective neck treatment . In contrast, other research has justified the use of unilateral elective neck irradiation based on tumor laterality . Data obtained from our analysis on ONB sidedness showed that the nodal spread patterns predominantly were bilateral irrespective of the degree of laterality of the tumor.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…This neoplasm is locally aggressive and commonly involves the nasal cavity, paranasal sinuses, and cribriform plate; there also may be extension into the cranial and orbital compartments. Many patients develop neck and distant metastasis during the course of their disease …”
Section: Introductionmentioning
confidence: 99%